Clinical introduction of MR-guided radiotherapy for esophageal cancer - Boekhoff, Mick Remo (Utrecht University, 2024)
Radiotherapy for esophageal cancer requires the use of imaging to localize and visualize the tumor. This thesis describes the use of magnetic resonance imaging in the radiotherapy treatment of patients with esophageal cancer. The first part of this thesis showed that esophageal cancer tumors are subject to position and shape changes throughout the treatment period. We have calculated that a treatment margin of 8-10mm would have been sufficient to provide sufficient target coverage for most patients. However, some patients showed extreme interfraction motion, which indicates the need for adaptive treatment strategies. The second part of this thesis reported on our experiences with an online adaptive, MR-guided radiotherapy treatment workflow. This adaptive strategy used day-to-day plan adaptation with smaller treatment margins of 6 mm. We have shown that this workflow is moderately feasible, mainly caused by the long treatment time of up to one hour per treatment session. We concluded that optimization of the presented clinical workflow is required. Nevertheless, the adaptive treatment strategy resulted in a dose reduction to the organs-at-risk compared to conventional treatment. This might allow for employment of improved treatment strategies, such as boosting strategies, to use this dose reduction to potentially improve the result of radiotherapy treatments of esophageal cancer tumors.
Keywords: mr-guided radiotherapy; esophageal cancer; adaptive radiotherapy; treatment margins; mr-linac; magnetic resonance imaging; radiotherapy; target coverage